2020
DOI: 10.1038/s41598-020-58411-x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of native IF1 downregulates glucose-stimulated insulin secretion by pancreatic INS-1E cells

Abstract: We have previously reported that transient knock-down of ATPase inhibitory factor 1 (IF1) by siRNA upregulates ATP levels and subsequently augments insulin secretion in model pancreatic β-cells INS-1E. Here we investigated how long-term IF1-overexpression impacts pancreatic β-cell bioenergetics and insulin secretion. We generated INS-1E cell line stably overexpressing native IF1. We revealed that IF1 overexpression leads to a substantial decrease in ATP levels and reduced glucose-stimulated insulin secretion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 52 publications
6
40
1
Order By: Relevance
“…According this hypothetical view, the preferential rapid expression of DAPIT and its binding into the vacant sites would then switch on ATP synthesis. DAPIT would then act reciprocally to the physiological inhibitor of the ATP synthase, the ATPase inhibitory factor IF1 [ 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According this hypothetical view, the preferential rapid expression of DAPIT and its binding into the vacant sites would then switch on ATP synthesis. DAPIT would then act reciprocally to the physiological inhibitor of the ATP synthase, the ATPase inhibitory factor IF1 [ 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that also the inhibitory factor IF1 of the mitochondrial ATP synthase belongs to the key proteins, ensuring the physiological range of the glucose sensor [ 11 , 12 ]. The IF1 slightly inhibits synthesis of ATP, thus setting the range for elevation of phosphorylating respiration and insulin release above 3-mM glucose [ 11 , 13 ], with half-activation between 3.5 and 4-mM and saturation above 8-mM glucose [ 11 , 12 ]. When such a slight in vivo inhibition was largely cancelled using the silencing of IF1, the elevation of respiration and OXPHOS occurred at very low glucose concentration approaching to zero [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are in line with the effects of IF1 overexpression or downregulation in cultured cells (Formentini et al 2012;Sánchez-Aragó et al 2013;Sánchez-Cenizo et al 2010). On the same line, the overexpression of IF1 in pancreatic β cells leads to a substantial decrease in ATP levels and in glucose-stimulated insulin secretion (Kahancová et al 2020), while the downregulation of the inhibitor protein in the same model causes an increase in mitochondrial respiration and in ATP levels leading to insulin secretion (Kahancová et al 2018).…”
Section: The Role Of the Inhibitor Protein If1 In Cancermentioning
confidence: 92%